Methyl-donors Induce Apoptosis and Attenuate Proliferation Pathways Mediated by Akt and Erk1/2 in Breast and Lung Cancer Cell Lines - Kiss, Eva; Forika, Gertrud; Mohacsi, Reka; Dank, Magdolna; Krenacs, Tibor; Takacs, Istvan; Nemeth, Zsuzsanna (Current Practice in Medical Science Vol. 9, 2022)
We aimed to explore how methyl-donor treatments affect the growth, proliferation, apoptosis and the related pathways in hormone positive invasive breast cancer (MCF7 and T47D) and NSCLC lung cancer (A549 and H1650) cell lines. Methyl-donors are employed as an adjunctive support in oncotherapy and play critical roles in physiological processes catalyzed by coenzymes of the B vitamins. Our theory was that methyl-donors may directly inhibit tumor development and proliferation in addition to helping patients tolerate cancer treatment. Methyl-donor treatment significantly reduced the proliferation in all investigated cell lines, possibly through the downregulation of MAPK/ERK and AKT signaling. These were accompanied by the upregulation of the pro-apoptotic Bak, Bax both in MCF7 and H1650 cells, at reduced anti-apoptotic Mcl-1 and Bcl-2 levels in MCF7 and H1650 cells, respectively. The treatment induced downregulation of p-p53(Thr55) was likely to contribute to protecting the nuclear localization and apoptosis inducing functions of p53. The features that are being offered are known to increase the sensitivity of cancer treatment. In light of this, the observations are consistent with the theory that methyl-donors may protect p53 activities by promoting apoptotic signaling by downregulating both the MAPK/ERK and the AKT pathways in breast and lung cancer cell lines. Our results can emphasize the importance and benefits of the appropriate dietary supports in cancer treatments. However, further studies are required to confirm these effects without any adverse outcome in clinical settings.